The Swedish market for wood briquettes : production and market development - Karlhager, Johan (SLU/Dept. of Forest Products, 2008)
Wood briquettes have constituted an important input to the Swedish energy system during the last two decades. However, the development of the production and markets for briquettes during the years 2000-2007 has not been studied in detail. The purpose of this study was to elucidate the state of the briquette industry. More specifically, the aims were to map the production of briquettes, describe the development of its markets, describe the production process, describe the producers and to examine the competitive situation for the producers. To collect data regarding the production and the producers, the markets, raw materials and company structures, a questionnaire was sent out to the producers during the fall in the year 2007. The results were then compiled and compared to previous studies. The description of the production process was mainly based on literature studies. The results were analyzed and related to M.E. Porter's Five force model to be able to describe the competitive environment for the briquette producers. The study was limited to production in Sweden and did not intend to cover a possible import of briquettes. Regarding the production process, the most common types of briquetting equipments were described. The results showed that the trend in the briquette industry was neutral, possibly negative. The turnover derived from briquette sales during the year 2006 was roughly a quarter of a billion SEK. The industry was very concentrated, with one producer accounting for 43 % of the aggregate production in the year 2006. Since the year 2000, the production of briquettes among the participating producers increased from some 210 000 tons (980 GWh) (Hirsmark, 2002) to some 280 000 tons (1 300 GWh) in the year 2006. The planned expansion of the production capacity was 3,8 % within the two years to come. A typical small scale briquette producer was a small saw mill, planing mill or a joinery using their by-products as raw material. 78 % of the briquettes are produced from purchased raw material. Planer shavings and saw dust were the raw materials used by the largest number of producers. Peat was another important raw material, used only in large-scale production. Pellet producers were considered being the most important raw material competitor and an analysis showed that pellets constituted a severe threat to the briquette industry as they were important substitute products to briquettes. The analysis also showed that the briquette buyers have a strong bargaining power in their negotiations with the producers.